Current status of biofuels (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This article provides an overview of the current situation of biofuels. It starts by examining biofuels in general with regard to the ongoing review of European objectives on consumption. Next, the underlying legal issues in this sector are analysed, focusing on the regulatory and planning framework and the tax system applied. This leads to discussion of the barriers that, hitherto, have prevented greater and quicker development of this alternative energy source. The article concludes with several proposals that aim to enhance development in this market.
Keywords: Biofuels; bioethanol; biodiesel; renewable energies; environment